Histopathology of stromal changes in tumor and tumor like lesions of breast using special stains - Reddy, Purushotham; M., Sindhuja (Tropical Journal of Pathology and Microbiology, 2019)
Background: The interplay between a tumor and its environment is exemplified by the morphological changes observed in the stroma of human breast cancer. Stromal changes in benign, premalignant and malignant lesions of breast helps in better understanding of disease process at the level of the tumor and host stromal reaction. Objectives- (1) To compare the stromal changes in benign, proliferative breast lesions and malignant breast lesion (2) To compare the stromal changes with grade of malignant breast lesions. Methodology: This was a one-year prospective study carried out in the department of Pathology KIMS, Hubballi, Karnataka, from January 2017 to December 2017. Excision biopsies and mastectomy specimens were collected in 10% buffered formalin and subjected to paraffin processing and embedding. Five-micron thick sections were cut and stained with H&E and special histochemical stains namely Masson’s Trichrome Stain (MTS) and Verhoeff’s Van Gieson (VVG) were used to study collagen and elastin content respectively. Results: The study included 121 cases of excision biopsies and mastectomies. Benign tumors and tumor like lesions showed more collagenosis compared to malignant lesions, whereas malignant lesions showed more elastosis compared to benign lesions. Grade III malignant tumors showed more elastosis when compared to Grade II and Grade I tumors. Conclusion: Tumor stroma in breast has been neglected in many studies. Upcoming prevention, diagnostic and therapy strategies and studies should be carried in an unbiased way, allowing analysis of stromal component in addition to classical investigations of the epithelial cancer component.